Adaptive Environmental Management A Practitioner's Guide - Allan, Catherine; Stankey, George Henry (Springer Netherlands : Imprint: Springer, 2009)
Adaptive management is the recommended means for continuing ecosystem management and use of natural resources, especially in the context of 'integrated natural resource management'. Conceptually, adaptive management is simply learning from past management actions to improve future planning and management. However, adaptive management has proved difficult to achieve in practice. With a view to facilitating better practice, this new book presents lessons learned from case studies, to provide managers with ready access to relevant information. Cases are drawn from a number of disciplinary fields, including management of protected areas, watersheds and farms, rivers, forests, biodiversity and pests. Examples from Australia, New Zealand, the USA, Canada, the UK and Europe are presented at a variety of scales, from individual farms, through regional projects, to state-wide planning. While the book is designed primarily for practitioners and policy advisors in the fields of environmental and natural resource management, it will also provide a valuable reference for students and researchers with interests in environmental, natural resource and conservation management.